2022
DOI: 10.1093/nar/gkac761
|View full text |Cite
|
Sign up to set email alerts
|

A fish herpesvirus highlights functional diversities among Zα domains related to phase separation induction and A-to-Z conversion

Abstract: Zalpha (Zα) domains bind to left-handed Z-DNA and Z-RNA. The Zα domain protein family includes cellular (ADAR1, ZBP1 and PKZ) and viral (vaccinia virus E3 and cyprinid herpesvirus 3 (CyHV-3) ORF112) proteins. We studied CyHV-3 ORF112, which contains an intrinsically disordered region and a Zα domain. Genome editing of CyHV-3 indicated that the expression of only the Zα domain of ORF112 was sufficient for normal viral replication in cell culture and virulence in carp. In contrast, its deletion was lethal for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…For a good example, see Fig. 4 of Diallo et al (2022). Confocal microscopy analysis revealed that CyHV-3 syncytia contained only nuclei expressing marginalized chromatin and so resulting from the fusion of infected cells at a late stage of infection (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…For a good example, see Fig. 4 of Diallo et al (2022). Confocal microscopy analysis revealed that CyHV-3 syncytia contained only nuclei expressing marginalized chromatin and so resulting from the fusion of infected cells at a late stage of infection (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Point mutations within Z domains also disrupt Z localization to biological condensates (Ng et al 2013;Gabriel et al 2021). For example, mutating Z-RNA-stabilizing amino acids within ORF112 leads to a disruption of the liquid-liquid phase separation necessary for the formation of condensates (Diallo et al 2022).…”
Section: Point Mutations To Z Domains Cause Aberrant Biological Funct...mentioning
confidence: 99%
“…3 B; Koehler et al 2017 ; Balachandran and Mocarski 2021 ). In fact, both E3L and ORF112 have been reported to outcompete binding of a Z-RNA antibody to its epitope ( Diallo et al 2022 ). E3L and E3L-like proteins are particularly important for preventing ZBP1 activation during early viral infection when viral RNAs are being heavily transcribed ( Koehler et al 2021 ).…”
Section: A Biological Function For Z-rna: Recruiting Winged Helix Pro...mentioning
confidence: 99%
See 2 more Smart Citations